Comparative Effects of Weight Loss Associated with a Consistent Volume of Exercise Within Education-Focused vs. Self-Regulation-Focused Obesity Treatments in Women - James J. Annesi (New Prairie Press, 2023)
Although exercise is generally included in behavioral weight-management treatments, its association with weight loss cannot be reconciled by its corresponding energy expenditures in formerly low-active adults with obesity. It has been suggested that the self-regulation needed to maintain exercise carries over to more controlled eating (i.e., coaction) and weight loss, with exercise-associated mood improvements also having positive impacts on eating behaviors and weight. To clarify these findings to improve behavioral interventions, women randomly assigned to community-based obesity treatments with either a self-regulation focus (n = 40) or educational focus (n = 25) were included in the present reanalysis of recent data. A requirement for inclusion within the present study was completion of 2 to 5 moderate exercise sessions per week (retrospectively assessed), regardless of treatment condition. Demographic data, weight, self-regulation, and negative mood did not significantly differ, by group, at baseline. Only reduction in weight significantly differed over 6 months, with a more pronounced improvement in the self-regulation-focused group. Changes in both self-regulation and negative mood significantly mediated the relationship between group and weight loss. Further regression analysis indicated that the entry of group significantly added to the prediction of weight change by (a) both self-regulation and mood change, and (b) change in self-regulation alone. For the present adherents to a moderate amount of exercise, improvements in self-regulation and mood explained a considerable amount of the variance (32%-37%) in weight loss over 6 months. However, analyses of effects from additional, possibly related, psychosocial variables based on theory and/or prior research (e.g., self-efficacy, emotional eating) will expand understandings of the value of moderate exercise beyond associated energy expenditures within varied behavioral obesity-treatment foci.